Susceptibility to Adrenal Crisis Is Associated With Differences in Cortisol Excretion in Patients With Secondary Adrenal Insufficiency - Vulto, Annet; van Faassen, Martijn; Kerstens, Michiel N.; van Beek, André P. (Frontiers in Endocrinology, 2022)
Objective To compare cortisol pharmacokinetics and pharmacodynamics mapped through several glucocorticoid sensitive pathways in patients on hydrocortisone substitution with or without an adrenal crisis. Design A post-hoc analysis of a previously conducted randomized controlled trial in patients with secondary adrenal insufficiency examining the effects of 2 weight-adjusted hydrocortisone doses. Methods Comparisons were primarily made on a hydrocortisone dose of 0.2-0.3 mg/kg/day for plasma cortisol and cortisone, 24-hour urinary steroid profile, the glucocorticoid sensitive tryptophan-kynurenine pathway, the renin-angiotensin-aldosterone system and aspects of quality of life. Variables of interest were also analyzed on the hydrocortisone dose of 0.4-0.6 mg/kg/day. Results Out of 52 patients, 9 (17%) experienced at least one adrenal crisis (AC+ group) and 43 did not develop an adrenal crisis (AC- group) during an observation period of 10 years. 24-hour urinary excretion of cortisol and cortisone were lower in the AC+ group (0.05 [IQR 0.03; 0.05] vs. 0.09 [0.05; 0.12] µmol/24h, P=0.01and 0.13 [0.10; 0.23] vs. 0.24 [0.19; 0.38] µmol/24h, P=0.04, respectively). No differences in pharmacokinetics of cortisol were observed. Kynurenine concentrations were higher in the AC+ group (2.64 [2.43; 3.28] vs. 2.23 [1.82; 2.38] µmol/L, P=0.03) as was general fatigue (Z-scores 1.02 [-0.11; 1.42] vs. -0.16 [- 0.80; 0.28], P=0.04). On the higher hydrocortisone dose urinary excretion of cortisol and cortisone was still significantly lower between the AC- and AC + group. The differences in glucocorticoid sensitive variables disappeared. Conclusion Patients susceptible to an adrenal crisis demonstrated differences in cortisol and cortisone excretion as well as in pharmacodynamics when compared to patients who did not experience an adrenal crisis, suggesting a biological predisposition in certain patients for the development of an adrenal crisis.